2019
DOI: 10.1038/s41598-018-37947-z
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor potential of new low molecular weight antioxidative preparations from the white rot fungus Cerrena unicolor against human colon cancer cells

Abstract: The aim of this study was to investigate the anticancer and antioxidant activities of low molecular weight subfractions isolated from secondary metabolites produced by the wood degrading fungus Cerrena unicolor. Human colon cancer cells (stage I) HT-29 and human normal colon epithelial cells CCD 841 CoTr were used in the research. The present study demonstrated that the low molecular weight subfractions exhibited inhibitory activity towards human colon cancer cells HT-29 at a concentration range of 25–200 μg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…The DPPH method performed according to the procedure proposed by Paduch et al 47 was used to determine the antioxidative properties of all mushroom samples. The procedure was also described in detail by Jaszek et al 48 and Matuszewska et al 49 .…”
Section: Methodsmentioning
confidence: 99%
“…The DPPH method performed according to the procedure proposed by Paduch et al 47 was used to determine the antioxidative properties of all mushroom samples. The procedure was also described in detail by Jaszek et al 48 and Matuszewska et al 49 .…”
Section: Methodsmentioning
confidence: 99%
“…Most studies have been conducted by specialized centers in the treatment of various cancers, acquired immunodeficiency syndrome (AIDS) and other illnesses caused by an imbalanced immune system. Studies on some mushroom species have also shown their ability to support the body in the interferon' synthesis (Matuszewska et al, 2019).…”
Section: Mushrooms: From Ethnobiology To Ethnopharmacologymentioning
confidence: 99%
“…One of the critiques of the unsuccessful clinical trials examining the effects of antioxidants on individuals at high risk for cancer was the use of pharmaceutical reagents as opposed to antioxidants derived from normal dietary components. Many natural compounds are a genuine source of bioactive compounds and many have been demonstrated to have anti-cancer activity [73,74]. With regards to antioxidant activity and in light of the studies that have been discussed above, one could surmise that a diet-derived compound that could be efficacious for cancer treatment would target cancer cells by increasing levels of intracellular ROS and thereby decreasing the capacity for cancer cells to survive.…”
Section: Dietary Prooxidantsmentioning
confidence: 99%